LABORATORY ALGORITHM FOR SCREENING TESTING OF PREGNANT WOMEN - Khudoyorova Madina,; Umarova Tamila Abdufattoyevna,; Uzoqov Sirojiddin Sultonovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Knowledge of the algorithm for examining pregnant women to identify fetal developmental defects is important for clinicians and district pediatricians. This allows them to better assess the condition of newborns, predict the child's developmental rate, and formulate preventive measures. Knowing the regulatory documents, methodology, and diagnostic capabilities of prenatal diagnosis methods for the fetal condition, the district pediatrician can help motivate future mothers to perform screening, especially if there are already children with developmental defects in the family [1,2].